Integracja europejska a wzrost gospodarczy w nowych krajach członkowskich - Rączaszek, Andrzej (European Integration Process and Economic Growth in New European Union Member States, 2008)
This study concerns the influence that the process of European integration has on the economic development of the new Member States. An extremely simplified way to observe this development is by analyzing the changes in GNP per capita. Taking into consideration the available statistical data published by the Central Statistical Office, the accomplishment of the assumed aim and verification of the thesis presented in this study are not easy. In the past the Central Statistical Office did not publish the data on some countries' economic development. Another difficulty has been the presentation of the GNP growth in the domestic currency. Therefore the first part of the analysis was devoted to converting the comparable values according to the exchange rate of the domestic currency against the American Dollar. Since 1986 the analyzed measure can be found as presented in $. The analysis shows the effects of the European policy of integrity, and indicates the expectation of such positive effects, also in the countries that joined the European Union in 2004 and 2007.(original abstract)
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 19, s. 29-43